Hemimasticatory spasm. Own experience of using botulinum neuroprotein type A - A. N. Korenko; A. V. Amelin; A. A. Timofeeva (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2022)
Нemimasticatory spasm (HMS) is a rare disorder of the nervous system, in which there are unilateral, violent spasms of the masticatory muscles innervated by the motor portion of the trigeminal nerve. The causes of HMS remain largely unexplored, but microvascular compression is most likely. Anticonvulsants, surgical treatment and botulinum therapy can be applied for the treatment of HMS.We presented a clinical case of HMS in a 38-year-old woman who had been suffering from this disease for 18 years. The diagnosis of HMS was established only 10 years after the first visit to the doctor. Spasms could occur up to several hundred times a day with a duration up to 15 seconds. The magnetic resonance imaging allowed to exclude neurovascular conflict. Electroneuromyography revealed axonal lesion of the right trigeminal motor root and spontaneous activity in the right masseter muscle. Anticonvulsant treatment was ineffective. The patient received botulinum therapy with a good treatment result.